2007
DOI: 10.1038/sj.eye.6702788
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C virus infection is not associated with Mooren's ulcer

Abstract: Aim To investigate the association between chronic hepatitis C virus (HCV) infection and Mooren's ulcer. Methods Eight patients from different parts of China who were diagnosed with Mooren's ulcer at the Zhongshan Ophthalmic Center, Guangzhou (China) were screened for chronic HCV infection. Mooren's ulcer was diagnosed by the typical ulcer morphology, detailed case history, physical examination, and comprehensive laboratory tests. All patients had serological screening for HCV infection. Results Six male and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The association is conflicting. According to Wang et al [132], Mooren corneal ulcerations are not associated with HCV infection.…”
Section: Mooren Corneal Ulcerationsmentioning
confidence: 98%
“…The association is conflicting. According to Wang et al [132], Mooren corneal ulcerations are not associated with HCV infection.…”
Section: Mooren Corneal Ulcerationsmentioning
confidence: 98%
“…Chronic pancreatitis and sclerosing cholangitis may result from the eventual fibrosis of the exocrine glands and pancreas in association with the biliary duct system in some cases of SS (Kaplan & Ike, 2002). Others have reported cases of acute and chronic pancreatitis in association with SS (Wang et al, 2008). One study demonstrated an immunogenic response to a protein isolated from the pancreas in patients with idiopathic chronic pancreatitis and SS (Kaplan & Ike, 2002).…”
Section: Gastrointestinal and Hepatobiliarymentioning
confidence: 99%